The Impact of Complete Aviation Services on Airport Service Performance at Class III Numfor Airport - Yulianto; Muhamad Sawir; Soesilo Wibowo (Britain International for Academic Research (BIAR) Publisher, 2023)
This study aims to analyze the development and use of Numfor Airport facilities, their impact on the performance of Numfor Airport, and the prioritized development and use of facilities at Numfor Airport. The research used mixed methods with the primary reliance on qualitative and quantitative data. While the qualitative data were obtained from interviews, the quantitative data were obtained from distributed questionnaires. The research participants and samples in this study amounted to 30 people, who were Numfor Airport employees, airline employees, and the public passengers. Quantitative data were processed using simple linear regression analysis. The results of the study show that 1) The development and utilization of facilities at Numfor Airport was far from optimal. 2) The development and utilization of facilities had a positive and significant effect on the performance of Numfor Airport. 3) It is necessary to prioritize the development and use of facilities at Numfor Airport for standardization of basic service facilities, procurement of the unavailable facilities, utilization of communication facilities, as well as procurement of special costs for transportation, postal and giro.